Do sentido aos significados do presídio de Clevelândia do Norte: repressão, resistência e disputa política no debate da imprensa - Brito, Edson Machado de (2008)
This work, entitled "From the sense to meanings of the North Clevelândia Prison: repression, resistance and political dispute in the debate of the press", proposes a view, in the press material, of the social struggles ,in which, the prison of Clevelândia North was inserted . Breaking with the perspectives that silence the dissident voices, this work proposes an understanding that the prison was an answer of State to tenentistas and anarchists movements, among others, the opposite movements in the period. The study points to another interpretation of the repressive actions of the republican government, considering that even if the prisoner s rights have been violated by torture, hunger, thirst, disease and death, the resistance not succumbed, and the Clevelândia theme returned to the political scene after the dissolution of the prison in December 1926, when the press started a strong debate, expressing the political disputes that was happening in the country at that time. The official historiography and its developments have treated the prison of Clevelândia as one of the repressive actions that produced the supposed defeat of the dissent. That historiography perspective keep silenced "the loser s voice," making an opinion, that the history is a process determined by the will of the State and of the "winners". This study comes to innovate the discussions about the prison of Clevelândia North, breaking with the side that interprets the prosecution, and specifically Clevelândia, as a factor of the dissident s resistance defeat. Here, Clevelândia North will be interpreted as a manifestation of the social struggles and the resistance against the oppression